Environmental & architectural phenomenology. Vol. 29, Number 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2018)
Vol. 29, No. 1, Winter/Spring 2018 (includes “Conferences,” “Symposium,” “Publishing items,” “Citations received;” memoriam for William Ittelson, written by John Hollander; book note of “An Anthropology of Landscape: The Ex-traordinary in the Ordinar;” book review by Thomas Barrie; essays by Barbara Erwine, Edward Relph, and Dennis Pohl; poems by Sheryl L. Nelms.)
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals